Incidental finding of a malignant tumour in an inguinal hernia sac - Qin, Rong; Zhang, Qiaoyu; Weng, Jianfeng; Pu, Yongdong (Contemporary Oncology/Współczesna Onkologia, 2014)
Metastatic carcinomas in hernial sacs are rare, especially in bilateral femoral hernias. Here we describe a 63-year-old female patient with metastatic carcinoma in bilateral femoral hernias. She was diagnosed incidentally during femoral hernioplasty. A diagnostic laparoscopy revealed metastatic nodules in the abdominal cavity. Subsequently, the patient underwent a laparotomy that did not show any evidence of primary lesions. A chemotherapeutic pump was implanted into the abdominal cavity during surgery for postoperative chemotherapy. The chemotherapy regimen included 5-Fu, hydroxycamptothecin, and pirarubicin, supplemented with high agglomerative staphylococcin. Forty-one months after surgery her disease was stable and no abdominal cavity, pelvis, liver or lung metastases were observed. Therefore, we suggest that abnormal hernial sacs may be the first clue to an underlying cancer, and should be sent for histological examination. Furthermore, if a patient is found to have metastatic abdominal cancer with no evidence of primary lesions, they would probably benefit from postoperative chemotherapy. This can be delivered using a chemotherapeutic pump implanted during surgery.